Water saturation effects on the tensile strength of rocks - Jong, Ming Chuan (2012)
In the design and construction of underground structures, the tensile strength of rocks is an important parameter to consider. As underground structures are often built below the groundwater table where rocks can be subjected to various degree of water saturation, this study aims to determine the effect of water saturation on the tensile strength of rocks.